2011
DOI: 10.1007/s13355-011-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in developmental times among four pure lines exhibiting specific wing form and body color in the brown planthopper, Nilaparvata lugens (Hemiptera: Auchenorrhyncha)

Abstract: Developmental times were compared among four pure lines of wing-dimorphic Nilaparvata lugens generated by successive selections for the following designated characteristics: blackish short-winged (BS), blackish long-winged (BL), yellowish brown short-winged (YS) and yellowish brown long-winged (YL). When the nymphs were reared on rice seedlings at low density, the developmental time was in the order of BS = BL \ Y-S = YL, while with an increase in rearing density, the time lengthened markedly in long-winged li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The four pure lines also differed in the nymphal developmental time in females in the following order: BS \ YS = BL \ YL lines (Morooka et al 2011). Further in the present study, we found differences in the pre-oviposition period as BS \ YS \ BL = YL, reflecting the differences in the pre-feeding period.…”
Section: Genetically Regulated Life-history Traitssupporting
confidence: 63%
See 1 more Smart Citation
“…The four pure lines also differed in the nymphal developmental time in females in the following order: BS \ YS = BL \ YL lines (Morooka et al 2011). Further in the present study, we found differences in the pre-oviposition period as BS \ YS \ BL = YL, reflecting the differences in the pre-feeding period.…”
Section: Genetically Regulated Life-history Traitssupporting
confidence: 63%
“…By extensive crossing experiments using these pure lines, Morooka (1992) proposed two major gene models for respective wing-form and bodycolor determination, one allele on an autosome and another allele on the X sex-chromosome. The four pure lines differ not only in body-color and wing-form expression, but also in developmental time, which is in the following order: BS \ YS = BL \ YL lines (Morooka et al 2011). These findings suggest the involvement of genes regulating body color and wing form in other life-history traits.…”
Section: Introductionmentioning
confidence: 79%
“…While in the case of N. lugens , the regulatory mechanism underlying body color may be much more intricate than our current understanding, just like in Locusta migratoria (Orthoptera), the pigment of body color is complex and can be modified by various factors, such as endogenous hormone and population density [ 50 ]. Moreover, previous research has demonstrated that both body color and wing morphology of N. lugens contribute to the regulation of development [ 51 ]. N. lugens is widely distributed among rice-growing regions in the tropical and temperate Asian Pacific region [ 52 ], and there are variations in migration and reproductive preferences among different regional populations of N. lugens [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%